The influence of family and housing environment on adolescent behavior in Seremban, Negeri Sembilan / Nureen Erlissa Darus and Nur Syazwani Ramli - Darus, Nureen Erlissa; Ramli, Nur Syazwani (2022)
The focus of this research is to investigate the influence of family and housing environment on adolescent behavior in Seremban. This study will be carried out in order to develop the study in identifying the influence of family towards adolescent behavior in Seremban, Negeri Sembilan. Moreover, the research is driven by the researchers' intention to determine the impact of housing environment on teenage behavior in Seremban, Negeri Sembilan. The research extended further to investigate the interaction between family and housing environment on adolescent behavior in Seremban. The research findings are crucial to understanding the impact of household and dwelling environment on adolescent behavior. Adolescent conduct is crucial since it determines their future endeavors based on the behavior displayed. It is critical to ensure that the family system is secure and that the teenager has a comfortable living environment. Adopting a content assessment method to investigate the influence of family and housing environment on teenage behaviour, the study used a quantitative strategy to collect data from 200 respondents through a questionnaire.